The Economic Impact of the Syrian Migration to Europe - Raygada, Sergio; Potužák, Pavel; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The present concern of most member countries in the EU is the short and long term impact of the influx of the Syrian refugees on their economy. The crisis in the Syrian territory has caused citizens to seek refuge and safety in nearby countries, thus creating an imbalance in the micro and macroeconomic activities of the receiving countries.The quality as well as the quantity of labor an economy can access has a direct influence on its GDP growth. An influx of labor to an economy as a result of the massive migration crisis caused by war, if not strategically harnessed and economically managed, could induce economic challenges. The aim of this study is to examine and estimate the economic impact that migrants coming to the EU due to the Syrian civil war will have by doing a regression analysis of immigration on the European Union labor market with variables such as wages, fiscal positions and employment. This research articulates from its findings that this has further augmented economies with available labor, and as a result, inducing an increase in unemployment, wages, and GDP growth.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses